A importância do ethos dos sujeitos em processos criminais: o convencimento do juízo e a sentença criminal - Quintas, Claudia Mastromauro Cerveira (2014)
This paper aims to verify which rhetoric strategies are used in legal discourses and how the characters' ethos is constituted in those discourses made along criminal cases. In the case analyzed, the father and the stepmother of a murdered child are the main suspects, and the sentences ended with the defendants conviction. In order to put in context the constitution process of the dissertation, historical and theoretical considerations about Classical Rhetoric and New Rhetoric were made, based on the studies of Aristotle, Chaim Perelman and Lucie Olbrechts-Tyteca, Michael Meyer, Olivier Reboul and Lineide do Lago Salvador Mosca. The studies of Luiz Antonio Ferreira were also used, referring to the principles of rhetoric analysis.The Constituição Federal da República Federativa do Brasil, in regard to magna laws, served as basis for the considerations of legal nature. The analysis is a result of the association of persuasion rhetoric techniques and the specificity of the construction of the ethos of the characters involved in a jury plenary, in order to point out how the discourses made in those scenarios were more or less persuasive and convincing. The selected piece shows the presence of several persuasive rhetoric strategies, as well as the way how the construction of the ethos of the characters is made in a discourse context. It can be seen the predominance of the epideictic genre and apodictic thinking, which start from probable or true premises and so, also bring speaker and audience close together. The characters involved in the analyzed discourses use passion movements to persuade the audience in order to obtain its adherence. Some rhetoric figures of presence and choice, like hyperbole and irony, are noticed in those discourses, what brings the speaker closer to the audience. The legal truth constitution, as shown in the analysis, starts from truthful premises and associates extrinsic and intrinsic evidence to conduct the audience. The rethoric context, surrounded by a universe of social values, is a major factor for the argumentative constitution and wields persuasive power. If the laws are vital for the promulgation of a sentence, the rhetoric path of all parts involved, done during the trial sessions, is key to the results obtained. It seems impossible to dissociate the logic conducting of the thinking without the potent association with the passion elements in the rhetoric constitution process of the act of judging, convicting or acquitting